Peran Public Relations Melalui Kegiatan Corporate Social Responsibility (CSR) Islami Berbasis Pemberdayaan Masyarakat - Rizqi Mahanani, Prima Ayu (STAI Miftahul Ula Nganjuk, 2015)
Image (good image) is a valuable asset to a company for participating into the carrying capacity in the face of increasingly fierce competition in this era of globalization. So it becomes a moral obligation and operations to build a good image of the company that is one of the Corporate Social Responsibility (CSR). This requires a strategic role of public relations in order to carry out CSR activities are on target and provide the benefit that aims to empower the community or the community at large. The strategic role of public relations is expected to be a strategic tool for management to achieve its goals. This paper attempts to analyze the descriptive CSR activities that have been carried out by two national companies / multinational in Indonesia and one government-owned enterprises are not just mere charity but aims to empower the people of Indonesia. With the intention of reviewing the CSR program that truly provide benefit to the independence of program beneficiaries, not become dependent, and not merely interpreted deeds alone company. So that later people perceive right to CSR which is a form of actualization of corporate responsibility and communication between the company and the public. Among prorgam CSR conducted by Telkomsel, Sinar Mas, and the Bank by making strategic empowerment activities with a primary focus on education and training, sports, health, agriculture, infrastructure, social, cultural, environmental maintenance, local business development, partnerships and small businesses. All the CSR program aimed at the development of human resources and better adapted to the real needs (real need) community.